Factfulness: Ten Reasons We’re Wrong About the World... - Choudhary, Jugal; Shree, Sonal (Prabandhan: Indian Journal of Management, 2019)
Whether researchers, teachers, corporate managers, philanthropists, or leaders of social organizations, our role requires us to make decisions that influence others. Hence, we have a responsibility to base our decisions on an unbiased view of the world around us. Unfortunately and unknown to us, our minds are wired to see things differently than they truly are. If you are like us, youâ€™ll want to correct this situation. Roslingâ€™s work, and particularly this book, has very significantly changed the way we perceive the world and we will be surprised if the book does not have the same effect on you. About the Author, Hans Rosling (1948â€“2017): Medical doctor, professor of international health, and renowned public educator. Adviser to the World Health Organization and UNICEF. Cofounded MÃ©decins Sans FrontiÃ¨res in Sweden and the Gapminder Foundation. TED talks with over 35 million views. Time magazine’s 100 Most Influential List.